The Olfactory Trail of Neurodegenerative Diseases - Rafael Franco; Claudia Garrigós; Jaume Lillo (Cells, 2024)
Alterations in olfactory functions are proposed as possible early biomarkers of neurodegenerative diseases. Parkinson’s and Alzheimer’s diseases manifest olfactory dysfunction as a symptom, which is worth mentioning. The alterations do not occur in all patients, but they can serve to rule out neurodegenerative pathologies that are not associated with small deficits. Several prevalent neurodegenerative conditions, including impaired smell, arise in the early stages of Parkinson’s and Alzheimer’s diseases, presenting an attractive prospect as a snitch for early diagnosis. This review covers the current knowledge on the link between olfactory deficits and Parkinson’s and Alzheimer’s diseases. The review also covers the emergence of olfactory receptors as actors in the pathophysiology of these diseases. Olfactory receptors are not exclusively expressed in olfactory sensory neurons. Olfactory receptors are widespread in the human body; they are expressed, among others, in the testicles, lungs, intestines, kidneys, skin, heart, and blood cells. Although information on these ectopically expressed olfactory receptors is limited, they appear to be involved in cell recognition, migration, proliferation, wound healing, apoptosis, and exocytosis. Regarding expression in non-chemosensory regions of the central nervous system (CNS), future research should address the role, in both the glia and neurons, of olfactory receptors. Here, we review the limited but relevant information on the altered expression of olfactory receptor genes in Parkinson’s and Alzheimer’s diseases. By unraveling how olfactory receptor activation is involved in neurodegeneration and identifying links between olfactory structures and neuronal death, valuable information could be gained for early diagnosis and intervention strategies in neurodegenerative diseases.